Research progress on the influence of exercise therapy of traditional Chinese medicine on the level of inflammation in patients with coronary heart disease - Wei, Qiuyang; Liu, Mingyu; Cui, Meize; Li, Yameng (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Coronary atheratherosclerotic heart disease, or coronary heart disease, also called ischemic heart disease, is a heart disease caused by coronary atherosclerosis that narrow or block the lumen, or caused by myocardial ischemia, hypoxia or necrosis caused by altered coronary functional spasm. In recent years, the Outline of the Healthy China 2030 Plan has clearly set out the development goal of reducing premature mortality from major chronic diseases, which regards the prevention and control of cardiovascular diseases in China as one of the health work in the future, to strengthen medical integration and non-health intervention, carry out traditional sports health projects, and promote the formation of health integration disease management and health service mode. In addition, the "13th Five-Year Plan" for the Development of Traditional Chinese Medicine clearly pointed out that the focus on chronic diseases and the concept of no disease treatment as the core, promote traditional Chinese medicine sports such as Taijiquan and Badaguan, and establish a number of clinical diagnosis and treatment plans and guidelines with ethnic characteristics. According to the planning requirements and the development of rehabilitation medicine in China, TCM related technology is gradually introduced in the field of cardiac rehabilitation, among which traditional TCM sports with Chinese cultural characteristics are applied to cardiac rehabilitation, and TCM sports therapy is carried out in the treatment mode of cardiac rehabilitation sports. At present, the inflammatory reaction drives the formation process of many atherosclerosis, which has attracted wide attention at home and abroad. A large number of studies have shown that exercise rehabilitation can relieve the atherosclerosis of coronary heart disease by reducing inflammatory factors. As a cardiac rehabilitation sports with Chinese cultural characteristics, the research shows that it can reduce the adverse events in patients with coronary heart disease, improve the quality of life and cardiopulmonary function, and reduce the medical burden of patients. But the current research is mostly traditional Chinese medicine exercise therapy on cardiopulmonary function and quality of life (walking ability, grip, sleep and mood) in patients with coronary heart disease, less to improve the pathogenesis of coronary heart disease, and there is no retrospective study on whether it can bring clinical benefits to patients by improving the state of inflammation. Therefore, on the basis of clear coronary heart disease is a typical low chronic inflammation, this research with inflammatory response as the breakthrough point, the effect of TCM movement therapy on inflammation index, and on the basis of the clinical application problems and future research suggestions, in order to provide support and basis for the application of traditional Chinese medicine sports therapy in the field of cardiac rehabilitation exercise. Methods: Through the Web of Science, Pub Med, Embase, Cochrane Library, EBSCO, CNKI, SinoMed, WanFang Data and VIP databases, To retrieve randomized controlled clinical trials (RCT) of TCM sports therapy (Taijiquan, Badaguan, Yijin Jing, Wuqinxi, and six-character formula) for intervention in patients with risk factors for coronary heart disease, The retrieval time limit is from library building to May 2021, Meanwhile, the references incorporated in the research literature were searched manually, To supplement the access to the relevant literature. The search strategy adopts the form of combining theme words and free words. Chinese search words mainly include: coronary disease, coronary atherosclerosis, myocardial ischemia, stable angina pectoris, Inflammatory factors, inflammation, inflammatory response, tai ji /tai chi /tai ji quan /tai chi quan, Baduanjin, Yijinjing, Wuqinxi, Liuzhijue, randomized controlled trial, etc. The English search words mainly include: coronary disease, coronary atherosclerosis, myocardial ischemia, stable angina pectoris, inflammatory factors, inflammation, inflammatory response, tai ji /tai chi /tai ji quan /tai chi quan, Baduanjin, Yijinjing, Wuqinxi, Liuzhijue, randomized controlled trial, etc. After the unrelated literature is excluded, the impact of traditional Chinese medicine exercise therapy on the level of inflammation in patients with coronary heart disease is reviewed, and the problems in clinical application and future research suggestions are proposed. Results: 267 literature was obtained, including 180 English literature and 87 Chinese literature. After excluding the unqualified literature, the effect of TCM exercise therapy intervention in patients with coronary heart disease was reviewed. From the perspective of intervention methods, it was found that Taijiquan was used as a cardiac rehabilitation intervention to improve the inflammatory status of patients, and it was more studied. From the perspective of the intervention results, it was found that traditional Chinese medicine exercise therapy has improved to different degrees in baPWV, blood lipid levels, endothelin and serum inflammatory factor levels, and hemodynamics in people with coronary heart disease, among which the improvement of inflammatory factors includes: IL-4, IL-6, IL-10, IL-18, TNF-a, MMP-9, hs-CRP, slCAM-1, sVCAM-1, Ga L-3, etc. Limitations and clinical research issues: (1) The selection of intervention methods for retrieval of literature is diverse, such as different types of Taijiquan, and different styles, which may affect the results of this study; This represents the possible lack of standardized cardiac rehabilitation exercise regimen in clinical studies; (2) The intervention cycle, intensity frequency and time of each intervention of the retrieved literature are also inconsistent, and the safety and adverse events of the intervention process are difficult to judge, representing the possible lack of scientific exercise intensity in TCM exercise therapy in clinical studies; (3) The outcome indicators of the retrieved literature are mostly phenomenon description, less further potential mechanisms of their phenomena, and more small sample single-center studies; more scientific, large sample, multi-center clinical randomized control of TCM exercise therapy is needed; (4) The search literature is both Chinese and English and lacking in other languages. Conclusion: In conclusion, TCM exercise therapy has good effect on the inflammatory state of patients with coronary heart disease, which may have a positive effect on alleviating vascular endothelial injury and reducing the accumulation of sediment in the arterial endometrium, further reducing artery obstruction and dysfunction, improving plate state and promoting blood oxygen supply. However, limited by the quantity and quality of relevant studies, the above conclusions also need to be verified by more high-quality empirical studies in the future.